2010
DOI: 10.1016/j.pain.2010.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inflammatory protein-1α mediates the development of neuropathic pain following peripheral nerve injury through interleukin-1β up-regulation

Abstract: In the present study, we investigated the role of the macrophage inflammatory protein-1alpha (MIP-1alpha) in the pathogenesis of neuropathic pain following partial sciatic nerve ligation (PSL) in mice. MIP-1alpha mRNA and its protein were dramatically up-regulated after PSL, and MIP-1alpha was localized on macrophages and Schwann cells in the injured sciatic nerve (SCN). PSL-induced long-lasting tactile allodynia and thermal hyperalgesia were prevented by the perineural injection of anti-MIP-1alpha (2ng). Intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
143
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(154 citation statements)
references
References 50 publications
9
143
2
Order By: Relevance
“…Elevated CCL11 serum levels are detected in mice and humans of old age, negatively regulating neurogenesis in the CNS (Villeda et al, 2011) and interfering with nervous system functions. We demonstrated that CCL11 directly interferes with Schwann cell myelination in vitro (Figure 6) and in vivo (Figure 7)—suggesting it as an important component of the dysregulated inflammatory nerve microenvironment impairing peripheral nerve remyelination in old age; a notion supported by age‐dependent increases in CCR5 expression (Supporting information Figure S3C), a CCL11 receptor reported to be expressed by Schwann cells and upregulated upon peripheral nerve injury (Kiguchi et al, 2010). Thus, elevated systemic CCL11 levels may be partly responsible for Schwann cell dedifferentiation and injury‐independent repair program activation (Figure 5) in intact old nerves.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Elevated CCL11 serum levels are detected in mice and humans of old age, negatively regulating neurogenesis in the CNS (Villeda et al, 2011) and interfering with nervous system functions. We demonstrated that CCL11 directly interferes with Schwann cell myelination in vitro (Figure 6) and in vivo (Figure 7)—suggesting it as an important component of the dysregulated inflammatory nerve microenvironment impairing peripheral nerve remyelination in old age; a notion supported by age‐dependent increases in CCR5 expression (Supporting information Figure S3C), a CCL11 receptor reported to be expressed by Schwann cells and upregulated upon peripheral nerve injury (Kiguchi et al, 2010). Thus, elevated systemic CCL11 levels may be partly responsible for Schwann cell dedifferentiation and injury‐independent repair program activation (Figure 5) in intact old nerves.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, similar to its ligand CCL11, CCR5 was upregulated in old age (Supporting information Figure S3C). CCR5 has been found expressed by both Schwann cells and macrophages, with significant upregulation upon peripheral nerve injury (Kiguchi, Maeda, Kobayashi, Fukazawa, & Kishioka, 2010). We hypothesized that CCL11 may be directly involved in regulation of Schwann cell behavior and tested this in a coculture system with DRG neurons and Schwann cells.…”
Section: Resultsmentioning
confidence: 99%
“…CCR1 is up-regulated in sensory neurons [11] and the spinal cord [7,12] after nerve injury and increased CCR1 mRNA has also been measured in rats 24 hr after receiving carrageenan [13], supporting its involvement in nociceptive processing. Functionally, it has been reported that some types of neuropathic pain can be alleviated by blocking CCR1 expression with siRNA [11], and that the administration of a CCR1 antagonist can prevent some types of murine bone cancer pain [10] and partially reduce writhing responses in mice receiving intraperitoneal acetic acid or mechanical hyperalgesia in inflamed mice [14]. Among the different chemokines able to activate CCR1 [15], CCL3 (MIP-1a, macrophage inflammatory protein-1a) and CCL5 (RANTES, reduced upon activation normal T-cell expressed and secreted) are particularly related to nociception.…”
mentioning
confidence: 77%
“…The stimulation of CCR1 expressed in nociceptors causes Ca 2+ influx and enhances capsaicin responsiveness [6], and the local administration of CCR1 agonists elicits nociceptive behaviours in mice [9,10]. CCR1 is up-regulated in sensory neurons [11] and the spinal cord [7,12] after nerve injury and increased CCR1 mRNA has also been measured in rats 24 hr after receiving carrageenan [13], supporting its involvement in nociceptive processing. Functionally, it has been reported that some types of neuropathic pain can be alleviated by blocking CCR1 expression with siRNA [11], and that the administration of a CCR1 antagonist can prevent some types of murine bone cancer pain [10] and partially reduce writhing responses in mice receiving intraperitoneal acetic acid or mechanical hyperalgesia in inflamed mice [14].…”
mentioning
confidence: 87%
See 1 more Smart Citation